VACCINATION AGAINST THE HPV - POSSIBLE PRIMARY PREVENTION FOR NEOPLASIA - Raluca Gabriela Ioan; Gabriela Adriana Dincă; Mioara Ionescu (Amaltea Medical Publishing House, 2013)
The frequency of different types of cancer (among which the cervical cancer covers 55%) etiologically correlated with the Human Papillomavirus (HPV) infection is worrying particularly amongst early ages. Demonstrating the presence and the oncogene role of some HPV types opened the way to prophylaxis by vaccination in a signifi cantly high percentage of cases. Vaccination against HPV was fi rst used in 2006 and it remarkably brought down the infection prevalence, with a good immunologic response and durable protection.